Meningkatkan Kemandirian Berliterasi dengan Metode PBL Materi Menghormati Orangtua Kelas 4 Fase B SD Negeri 8 Pardomuan – Samosir - Rawana Isabella Sitanggang; Hartutik Hartutik; Sugiyana Sugiyana (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
The majority of students in Grade 4 Phase B SD Negeri 8 Pardomuan face difficulties in understanding the value of respecting parents due to low literacy independence. As a result, students tend to be passive in comprehending and connecting texs. In addition, the teacher has not yet determined a student-centered method in the learning process.This study aims to improve literacy independence amon Grade 4 Phase B students at SD Negeri 8 Pardomuan in the subjectof catholic Religion and Character Education, particularly in the topic Respecting Parent. To address this issue, an engaging learning method is required to enhance literacy independence. The chosen method is Problem Based Learning (PBL), wich has proven affective and serves as a motivational trigger for students. It emphasizes student activity and ancourrages literacy independence by focusing on the “independent dimension of the Pancasila Student Profil. The goal is to strengthen affective aspects during the learning process. This classroom action Research was conducted in two cyles and consisted of four stages: planning, implementation, evaluation, and reflection. The study involved 8 students. The result showed significant improvements in student learning outcomes on the topic Respecting Parents, particulary in the Independent dimension. The average score in cycle I was 64.4%, wich increased to 91.1% in cycle II again of 26.7%.cognitive test result also improved, with the average score rising from 78 in cycle I to 88 in cycle II an increase of 12.82%.Reflections indicated that strengthening the affective aspect helps students improve their literacy independence. The findings affirm that the PBL method can effectively enhance students literacy independence and help them meet learning objectives.